A Little Mystery, Mythology, and Romance: How the “Pigmy Flint” Got Its Name - Piper Stephanie F. (Open Archaeology, 2022)
The term “pigmy flint” was coined in 1895 and frequently used to describe small flint implements, many of them microliths, in British and Irish archaeology during the earliest decades of the 20th century. It was briefly adopted in France over a decade later to describe the same tools, translated as “silex pygmée”, the simultaneous emergence of the French term “microlithique” saw the latter become more widely used, however. The Anglicised “microlith” was not commonly incorporated into British archaeological terminology until the mid-1920s. The international interplay in nomenclature and the changing nature of the terminology that was used to describe such “very small implements of flint” are mirrored by the different attitudes of early archaeologists to these tools. They were dismissed by some and marvelled at by others. Moreover, the definitions that surround these terms are embedded within the problematised acceptance of the “Mesolithic” as a distinct chronological entity. The recognition of morphologically similar “pigmies” across the world sparked questions of migration, function, and chronology – in its broadest culture-historical sense – thus shaping the way in which this microlithic technology and its association with the Mesolithic came to be understood by early archaeologists in Western Europe.